Establishment of a New Real-Time Molecular Assay for the Detection of Babanki Virus in Africa - Martin Faye; Mathilde Ban; Fatou Kiné Top; El Hadji Ndiaye; Fatou Diène Thiaw; Gamou Fall; Moussa Moise Diagne; Amadou Alpha Sall; Mawlouth Diallo; Valérie Choumet; Ousmane Faye (Viruses)
Babanki virus is a subtype of the Sindbis virus, a widespread arthropod-borne alphavirus circulating in Eurasia, Africa, and Oceania. Characterized by rashes and arthritis, clinical infections due to Sindbis were mainly reported in Africa, Australia, Asia, and Europe. However, its sub-type, Babanki virus, was reported in Northern Europe and Africa, where its epidemiology potential remains poorly understood. The diagnosis of alphaviruses is mainly based on serological testing and conventional PCR methods, which have considerable limits. In this study, we developed a real-time qRT-PCR assay for the detection of Babanki virus. The analytical sensitivity and specificity of the newly established assay were evaluated using in vitro standard RNA and related viruses relevant to the African context, respectively. In addition, its diagnostic sensitivity was assessed using a subset of Babanki virus-positive and -negative mosquito pools collected from the field. The new real-time qRT-PCR assay exhibited a 100% specificity, a 95% detection limit of 1 RNA molecule/reaction, and a diagnostic sensitivity of up to 120 pfu/reaction. This newly established assay could be useful not only for the detection of Babanki virus during epidemics but also in future experimental and surveillance studies focusing on their epidemiology and pathogenicity.